Desalination membranes by deposition of polyamide on polyvinylidene fluoride supports using the automated layer-by-layer technique. Issue 7 (3rd May 2022) - Krizak, Daniel; Abbaszadeh, Mahsa; Kundu, Santanu
ABSTRACT: Thin-film composite (TFC) membranes with a polyamide (PA) active layer are the industry standard in desalination applications. The layer-by-layer (LbL) approach provides more precise control over the properties of this active PA layer. The automated spin-assisted LbL version of this approach then minimizes human error and improves repeatability. To improve durability of these membranes, more robust supports are desired, such as polyvinylidene fluoride (PVDF). The use of the LbL technique on this support requires an interlayer to enable the deposition onto the PVDF. In this case, levodopa was utilized to coat the PVDF prior to deposition of the PA layer. The membranes exhibited moderate permeability and higher selectivity for sodium chloride under typical brackish water conditions compared to commercially available NF membranes. This novel interlayer further expands on the automated spin assisted LbL approach, enabling deposition of PA onto a support.